Rekonstruksi Metodologis Wacana Keagamaan Muhammad Shahrour - Tsuroya Kiswati (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2010)
The main objective of this paper is to explore the hermeneutical method of Muhammad Shahrour in his interpretation of the holy Qur??n. Shahrour?the Syrian scholar- is known for his view that each and every word in the Qur??n has an independent and unique meaning. In other words, for him no two words share the same meaning in the Qur??n. Hence, he distinguishes between the Qur??n and the Kitab and reckons that the two words imply two different things conceptually. But Shahrour is also known for his interpretation that would pay a good deal of attention to the historical, social, literal and linguistical backgrounds of the verses of the Qur??n. And this he considers as the valid form of exegesis capable of unearthing the hidden meaning of the Qur?an. This paper argues that the hermeneutical method of Shahrour necessitates that the verses of the Qur??n must be interpreted in such a way as to suit the demands of time, and to do that one must not only understand the meaning of the text but also the meaning of its context.